2021
DOI: 10.3390/ph14060551
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Modulatory Effects of Fever-Range Hyperthermia on the Response of Breast Cancer Cells and Macrophages to Mistletoe (Viscum album L.) Extract

Abstract: Heat utility as a critical component of fever is often ignored, although the symptom is observed in many medical conditions. Mistletoe extract (ME) is an adjunctive medication prescribed to cancer patients. The increase in body temperature is frequently observed in patients following ME administration. Nevertheless, the impact of this fever on the effectiveness of therapy is unknown. Therefore, we aimed to investigate the effect of fever-range temperatures on ME-treated breast cancer cells and macrophages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…We revealed that FRH alone induces an M2-like phenotype manifested by increased expression of CD163, IL-10, and Arg-1. However, we observed an increased level of pro-inflammatory TNF-α, which was in line with our previous experiments showing that FRH-treated macrophages can release pro-inflammatory cytokines such as IL-6 and IL-β [4]. Other authors have found that stimulation of RAW264.7 cells induces a heightened responsiveness to lipopolysaccharide in a model of inflammatory responses when compared to J774A.1 macrophages [28].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We revealed that FRH alone induces an M2-like phenotype manifested by increased expression of CD163, IL-10, and Arg-1. However, we observed an increased level of pro-inflammatory TNF-α, which was in line with our previous experiments showing that FRH-treated macrophages can release pro-inflammatory cytokines such as IL-6 and IL-β [4]. Other authors have found that stimulation of RAW264.7 cells induces a heightened responsiveness to lipopolysaccharide in a model of inflammatory responses when compared to J774A.1 macrophages [28].…”
Section: Discussionsupporting
confidence: 92%
“…Despite reported benefits in the treatment of chronic diseases such as rheumatic diseases or cardiovascular disorders [3], the molecular changes induced by FRH remain poorly characterized. In our previous studies on mistletoe extract, we observed that macrophages are heat-sensitive cells that respond to heat with increased expression of pro-inflammatory cytokines such as interleukin (IL)-1β and IL-6 [4]. This observation is in accordance with other studies that demonstrated that elevated temperature can decrease the activation threshold required for the production of effector molecules in macrophages [5].…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cellular and animal experiments have demonstrated that mistletoe induces apoptosis and inhibits metastasis by targeting the STAT3-FOXM1 pathway in BC [181]. Mistletoe exerts distinct effects on BC cells and macrophages, influencing cell viability, ROS generation, cell cycle arrest, and inflammation, all of which are modulated by changing in fever-range hyperthermia [182]. Although clinical trials have been conducted to investigate the potential of mistletoe in mitigating the side effects and enhancing anti-cancer effects, only a few numbers of animal studies have delved into the underlying molecular targets and mechanisms of its actions.…”
Section: Mistletoementioning
confidence: 99%